2010
DOI: 10.1002/cbic.200900565
|View full text |Cite
|
Sign up to set email alerts
|

Phosphopantetheinylation and Specificity of Acyl Carrier Proteins in the Mupirocin Biosynthetic Cluster

Abstract: Acyl carrier proteins are vital for the biosynthesis of fatty acids and polyketides. The mupirocin biosynthetic cluster of Pseudomonas fluorescens encodes eleven type I ACPs embedded in its multifunctional polyketide synthase (PKS) proteins plus five predicted type II ACPs (mAcpA-E) that are known to be essential for mupirocin biosynthesis by deletion and complementation analysis. MupN is a putative Sfp-type phosphopantetheinyl transferase. Overexpression of three type I and three type II mupirocin ACPs in Esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…Our previous studies with mupN , which encodes an Sfp-like PPTase 24 , had shown only that it is needed to activate at least some of the ACPs encoded in the mup cluster 18,25 . Shields et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies with mupN , which encodes an Sfp-like PPTase 24 , had shown only that it is needed to activate at least some of the ACPs encoded in the mup cluster 18,25 . Shields et al .…”
Section: Discussionmentioning
confidence: 99%
“…162 Indeed, when mupN was deleted, mupirocin production was abolished, and it was shown in vitro that both type I and type II ACPs were modified by this PPTase. 43 In contrast to P. aeruginosa , P. fluorescens has two PPTases, PfPcpS and MupN, at its disposal, and it remains a question whether PaPcpS and PfPcpS have different substrate specificity.…”
Section: Importance In Primary and Secondary Metabolismmentioning
confidence: 99%
“…10). 28,[60][61][62] The initially reported incorporation of a cleaved acetate group was conrmed through a combination of isotope labelling and gene cluster comparison. 25,63 The mechanism of such b-branching was elucidated in the bacillaene biosynthetic pathway in vitro by Calderone et al using a combination of biochemical assays and mass spectrometry.…”
Section: Endo-b-methyl (1)mupirocin and Bacillaenementioning
confidence: 99%